Individual and combined effects of cinnamon powder and vacuum packaging on the shelf life of Suman sa Gata - Panganiban, Elisha Marjel B.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
The study aimed to determine the effect of cinnamon powder and vacuum packaging on the quality of Suman sa gata. Suman with varying levels of cinnamon powder (1, 2 and 3% w/w) were found to be acceptable by consumer panelists, with an average Hedonic rating of 6, equivalent to ―like slightly‖. Further analysis of suman with 3% cinnamon powder was conducted by producing suman with or without vacuum packaging and monitored for changes in physico-chemical (pH, Aw, Firmness), microbiological and consumer acceptance of appearance, aroma, texture, flavor and overall acceptability upon storage at room temperature. The pH of suman with cinnamon powder across storage days, were below the control sample (suman without cinnamon powder and vacuum packaging) perhaps due to oxidation of trans-cinnamaldehyde to cinnamic acid. The water activity on the other hand increased for samples with cinnamon powder. Firmness of all samples increased upon storage, probably due retrogradation of starch, however, samples with cinnamon powder were noticeably less firm. Cinnamon powder and vacuum packaging of suman were able to inhibit the growth of spoilage microorganism for at least 10 days. Addition of cinnamon, coupled with vacuum-packing can extend the shelf life of suman sa gata, based on acceptance of flavor, from three days to at least one week, at room temperature. This considerable increase in stability will be of great impact to suman makers.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Cinnamon -- Philippines; Suman